Comparison of 3-level anterior cervical discectomy and fusion and open-door laminoplasty in cervical sagittal balance: A retrospective study - Wang, Wenhao; Huang, Yixue; Wu, Zhikai; Hu, Xiayu; Xiang, Pan; Liu, Hao; Yang, Huilin (Frontiers in Surgery, 2022)
Objective To compare the clinical efficacy and radiological outcomes of 3-level anterior cervical discectomy and fusion (ACDF) and open-door laminoplasty (LP). Methods A total of 74 patients from January 2017 to January 2020 were enrolled in this retrospective study. There were two groups. Group A (30 cases) received 3-level ACDF, while Group B (44 cases) received open-door LP. Clinical evaluation included perioperative parameters, Neck Disability Index (NDI), and Japanese Orthopaedic Association (JOA) scores. Radiological evaluation included cervical curve depth (CCD), C2-7 angle, C2-7 sagittal vertical axis (cSVA), C7 slope (C7S) and T1 slope (T1S). Results Perioperative parameters including blood loss, drainage volume after surgery and hospital stay of patients in Group A were significantly less than those in Group B (P<0.001). NDI scores decreased and JOA scores increased significantly after surgery in both groups (P<0.05). There was significant difference in both scores post-operatively and at 1 month after surgery between two groups (P<0.05). CCD and C2-7 angle of Group A increased significantly post-operatively, at 1 month after surgery and at FFU (P<0.05). There was significant difference in CCD and C2-7 angle between two groups post-operatively, at 1 month after surgery and at FFU (P<0.05). T1S increased significantly in Group A post-operatively and at 1 month after surgery (P<0.05). Conclusions 3-level ACDF and open-door LP achieved favorable clinical outcomes and ACDF benefited patients in the early stage of rehabilitation. Compared with open-door LP, 3-level ACDF had advantages of reconstructing cervical lordosis with increased CCD and C2-7 angle.